Crown ethers as new curing agents for epoxy resins. Issue 12 (30th October 2017) - Fraga López, Francisco; Vázquez Barreiro, Eva C; Jover, Aida; Martínez Ageitos, José Manuel; Rodríguez, Eugenio; Vázquez Tato, José
Abstract: Different crown ethers (4‐aminobenzo‐15‐crown‐5 (4‐aminobenzo‐15‐C5), 1, 4, 10, 13‐tetraoxa‐7, 16‐diazacyclooctadecane (diaza‐18‐crown‐6), tetraazacyclododecane‐1, 4, 7, 10‐tetraacetic acid (H4 DOTA) and tetraazacyclododecane‐1, 4, 7, 10‐tetraacetamide (H2 ODDA)) were used as curing agent for bisphenol A diglycidyl ether (BADGE, n  = 0). The maximum enthalpy change for all systems except that formed by the epoxy resin with H4 DOTA corresponds to a stoichiometric ratio, since from this value the reaction enthalpies decrease when the proportion of epoxy increases. Heteropolymerization reaction occurs in all the crown ethers. Etherification reactions occur at temperatures much lower (30 °C less) than for the porphyrin systems studied in which a second signal appears at 300 °C. The etherification is evidenced by a slight shoulder in the thermograms for H4 DOTA and H2 ODDA. The systems BADGE ( n  = 0)/4‐aminobenzo‐15‐C5 and BADGE ( n  = 0)/diaza‐18‐crown‐6 improve the thermal stability of the epoxy resin by 30 °C approximately while the improvement for BADGE ( n  = 0)/H4 DOTA and BADGE ( n  = 0)/H2 ODDA is about 60 °C. © 2017 Society of Chemical Industry Abstract : Different crown ethers (4‐aminobenzo‐15‐crown‐5 (4‐aminobenzo‐15‐C5), 1, 4, 10, 13‐tetraoxa‐7, 16‐diazacyclooctadecane (diaza‐18‐crown‐6), tetraazacyclododecane‐1, 4, 7, 10‐tetraacetic acid (H4 DOTA) and tetraazacyclododecane‐1, 4, 7, 10‐tetraacetamide (H2 ODDA)) have been used as curing agent for BADGE n  = 0.